Genomic epidemiology and longitudinal sampling of ward wastewater environments and patients reveals complexity of the transmission dynamics of blaKPC-carbapenemase-producing Enterobacterales in a hospital setting - Stoesser, N; George, R; Aiken, Z; Phan, HTT; Lipworth, S; Quan, TP; Mathers, AJ; De Maio, N; Seale, AC; Eyre, DW; Vaughan, A; Swann, J; et al. (Oxford University Press, 2024)
Background Healthcare-associated wastewater and asymptomatic patient reservoirs colonized by carbapenemase-producing Enterobacterales (CPE) contribute to nosocomial CPE dissemination, but the characteristics and dynamics of this remain unclear.